Религия, культура и общество в контексте глобалистики - Сахроков, Владимир А. (International Dialogues on Education Journal, 2014)
The author focuses on the basic items outlined in his book „Religion, Culture and Society in the Context of Globalization” (Сахроков [Sakhrokov], 2012). A special part characterizes the interrelations of cultures and religions in a non-traditional way through a perspective of the so-called „golden proportion”. The article also dwells on social aspects of cultures and religions such as the social functions of religions and the dynamics of spirituality development in Christianity and Islam on a comparative level, as well as on the socio-natural relations between cultures and religions. Of no least importance, as highlighted in the article, are such crucial issues in the contemporary world as an Islamo-Christian dialogue, theological education and sustainable development.